2016
DOI: 10.1073/pnas.1617786113
|View full text |Cite
|
Sign up to set email alerts
|

Map reading, navigating from maps, and the medial temporal lobe

Abstract: We administered map-reading tasks in which participants navigated an array of marks on the floor by following paths on hand-held maps that made up to nine turns. The burden on memory was minimal because the map was always available. Nevertheless, because the map was held in a fixed position in relation to the body, spatial computations were continually needed to transform map coordinates into geographical coordinates as participants followed the maps. Patients with lesions limited to the hippocampus (n = 5) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Thus, in these studies, lesions limited to the hippocampus did not affect the ability to judge the structural coherence of objects, objects embedded in scenes, or scenes themselves. This conclusion is in accord with our earlier findings that the hippocampus is also not needed for a variety of other spatial tasks, so long as the tasks do not depend on long-term memory (Rungratsameetaweemana & Squire, 2018;Urgolites et al, 2016Urgolites et al, , 2017Kim et al, 2011Kim et al, , 2015Kim, Borst, et al, 2013;Kim, Sapiurka, et al, 2013;Shrager et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, in these studies, lesions limited to the hippocampus did not affect the ability to judge the structural coherence of objects, objects embedded in scenes, or scenes themselves. This conclusion is in accord with our earlier findings that the hippocampus is also not needed for a variety of other spatial tasks, so long as the tasks do not depend on long-term memory (Rungratsameetaweemana & Squire, 2018;Urgolites et al, 2016Urgolites et al, , 2017Kim et al, 2011Kim et al, , 2015Kim, Borst, et al, 2013;Kim, Sapiurka, et al, 2013;Shrager et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In these circumstances, patients with hippocampal lesions might have been disadvantaged due to their memory impairment. In our own studies of spatial tasks, where we attempted to minimize the contribution of long-term memory (by limiting the number of stimuli or by using trial-unique stimuli), hippocampal patients performed as well as controls (path integration, Kim, Sapiurka, Clark, & Squire, 2013;Shrager, Kirwan, & Squire, 2008; visual discrimination of scenes, Kim et al, 2011;spatial imagery, Kim, Borst, et al, 2013; scene construction, Kim, Dede, Hopkins, & Squire, 2015; map reading and navigation, Urgolites, Kim, Hopkins, & Squire, 2016; topographical memory with shifts of viewpoint, Urgolites, Hopkins, & Squire, 2017; scene construction with shifts of viewpoint, Rungratsameetaweemana & Squire, 2018). For a report of impaired performance in a task using trial-unique stimuli, see Lee et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an ongoing debate on whether the hippocampus is actually needed to navigate in familiar environments (see e.g. (53)(54)(55)(56)). Several studies indicate that the hippocampus is important primarily in situations of navigation that require the formation of new memories (57).…”
Section: Discussionmentioning
confidence: 99%
“…The medial temporal region includes the hippocampus, the subicular complex and the parahippocampal cortical regions, which collectively play a critical role in the encoding, storage and active manipulation of cognitive maps ( 38 ). Accordingly, past research has demonstrated that patients with lesions to the medial temporal lobe exhibit deficits with spatial memory, including recalling locations, drawing maps of the environment and making judgments about the distance and proximity of locations ( 39 ). Similar spatial memory deficits have been observed in patients with AD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%